Corporate governance - Kim, Kenneth A. (Prentice Hall, 2007)
The first of its kind, Nofsinger provides an overview of our corporate governance system in a flexible, modular format. Today, the term "corporate governance" is familiar to almost everyone. Unfortunately, its familiarity in our society comes about because of revelations of one shocking corporate scandal after another: executives caught pilfering from their firms; accountants helping companies doctor their financial numbers; analysts irresponsibly hyping internet stocks. Nofsingeris organized into chapters that discuss each corporate governance mechanism. Every chapter is organized in the same way, and each chapter is self-contained. Each chapter begins with a detailed overview of the monitor or monitoring mechanism, and then highlights potential problems.